Propuesta de Mejoramiento para el Indicador de Gestión del Lead Time de la Agencia de Aduanas Agecoldex (2023)
This paper describes the activities and functions carried out as an intern at the Agecoldex Customs Agency Level 1 S.A, specifically in the customer service area (SAC) in support of the import operational area. At the same time, the knowledge acquired during the academic program of International Trade is related to the functions assigned in the company and a value proposition is developed in order to optimize a specific process within the company.